Strategies for Enhancing the Efficiency of China's Integrated Transport System - Chunfang Lu; Guangzhi Jia; Yongbo Zhang; Liuying Wang; Wenqi Mu; Fangcan Zhao (中国工程科学)
An integrated transport system comprises various modes of transportation such as railways, highways, waterways, and aviation, and improving the efficiency of this system is crucial for enhancing residents' quality of life, optimizing social resource allocation, and promoting balanced regional development. Consequently, it is necessary to analyze the factors that restrain the improvement in transport efficiency and explore pathways and strategies for efficiency improvement. This study elucidates the concept of the integrated transportation system as well as the essence of efficiency improvement, and outlines the basic requirements for enhancing the system's efficiency in the new era. Moreover, it analyzes the current status of efficiency improvement of China's integrated transport system and identifies the constraining factors in terms of layout structure, utilization efficiency, durability and reliability, management effectiveness, and investment debt pressure. Furthermore, the following suggestions are proposed to promote China's integrated transport system to a new stage of development: (1) optimizing the layout and structure of the integrated transportation infrastructure, (2) promoting the integration of infrastructure, energy, information, and service networks, (3) enhancing the durability and reliability of existing transportation infrastructure, (4) improving the organizational efficiency and management performance of the integrated transport system, and (5) optimizing future investments in the construction of the integrated transport system.